Current state of fiberglass post - Lamas Lara, César (2015)
In the reconstruction of endodontically treated teeth we have many clinical possibilities and this is due to the advancement of materials and technologies. The job of the professional is to be qualified to accomplish the current procedures modifying its protocols. The most commonly materials used for cementing posts are glass ionomer, resin modified glass ionomer and resin cements. For all these materials we need to obtain a homogeneous, thin layer without cracks or bubbles. These characteristics are difficult to achieve because of especial characteristics of root canal. A review of literature on the materials and techniques commonly used in the cementation of prefabricated post is presented and a protocol that can guide the clinician to obtain predictable and reliable results over time is proposed.